Activation of Neurogenesis as a Prerequisite for Intensifying the Process of Learning Foreign Languages in a Non-Linguistic Environment - Raisa Martynova (Pedagogical Discourse, 2024)
The article examines the problem of activation of neurogenesis as a prerequisite for the intensification of the process of learning foreign languages in a non-linguistic environment. The foundation of the research was neurogenesis phenomenon as a multi-stage process of the formation of new nerve cells and associative relationships between them in the central nervous system, namely in the neocortex, which is considered to be its adaptive function. The conducted research made it possible to come to the following conclusions: 1) neurogenesis in the neocortex is such a psychophysiological phenomenon that ensures the mental development of a person in general sense and mastering a foreign language in particular; 2) neurogenesis in the preschool-age children is the most active process due to the presence of the largest number of genetically derived neurons. In the process of their activation and unification, as a result of the plasticity of the neurostructures of the cerebral cortex, the rapid development of children and the possibility of their successful learning a foreign language take place. But it occurs under the condition that training is carried out on the basis of mastering an interesting activity for the children conducted in a foreign language; 3) activation of neurogenesis in children of different age groups: of primary school age is achieved on the basis of intuitive mastering of linguistic phenomena in the process of topical speaking in a foreign language; of middle and high school age is achieved on the basis of conscious mastering linguistic phenomena in the process of movement gaming and the formation of a foreign language dynamic stereotype; 4) the activation of neurogenesis in students is achieved on the basis of their integrated mastering a professional subject and a foreign language as a means of learning it. Intensification of brain activity is provided by the formation of neural connections between different content units; and the availability of such activities for the majority of students is provided by the didactic stages of the integrated learning process; linguistic-conceptual, subject-speech and subject-activity.